KIAI LOKAL ANTARA PENGHAMBAT DAN PENYELAMAT DALAM PELAKSANAAN UNDANG-UNDANG PERKAWINAN NO. 1 TAHUN 1974 - Yasin Yasin (Program Studi Hukum Keluarga Islam, 2016)
This article observes the role of local ulama (kyai) in the implementation of Marriage Law No 1/1974 which is already more than four decades. Local ulamas have always been prominent figures for Muslim community. The Marriage law brought about new perspectives on marriage. Meanwhile, local ulamas have reknownedfor their firm hold of fiqh books somehow different from – not to say contradict to – the Law. How then local ulamas supervise and govern local people in the implementation of Marriage Law in the matters ofmarriage registration, and divorce before the Court.